The Mediating Roles of Attitude Toward COVID-19 Vaccination, Trust in Science and Trust in Government in the Relationship Between Anti-vaccine Conspiracy Beliefs and Vaccination Intention - Capasso, Miriam; Caso, Daniela; Zimet, Gregory D. (Frontiers in Psychology, 2022)
Since the outbreak of COVID-19, many conspiracy theories have spread widely, which has the potential to reduce adherence to recommended preventive measures. Specifically, anti-vaccine conspiracy beliefs can have a strong negative impact on COVID-19 vaccination attitude and intention. The present study aimed to clarify how such beliefs can reduce vaccination intention, exploring the possible mediating roles of attitude toward vaccination, trust in science, and trust in government, among a sample of 822 unvaccinated Italian adults (Women = 67.4%; Mage = 38.1). Path analysis showed that anti-vaccine conspiracy beliefs influenced intention to get vaccinated both directly and indirectly through the mediating effects of attitude, trust in science, and trust in government. In particular, the simple mediating effect of attitude was the strongest one, followed by the serial mediating effect of trust in science and attitude itself. Findings provide insights into the design of interventions aimed at reducing misinformation and subsequent vaccine hesitancy.